Hydraulic stress limits thermal acclimation in trees under chronic drought - Alyssa T. Kullberg; Arianna Milano; Alvaro Poretti; Yike Ma; Patrick Favre; Kate M. Johnson; Giovanni Bortolami; Maxwell Bergström; Thibaut Juillard; Jin Wu; Zhengfei Guo; Jonas Gisler; et al. (Proceedings of the National Academy of Sciences, 2026)
The capacity of trees to withstand intensifying hot drought events depends on the coordination between hydraulic safety and leaf thermoregulation, yet the limits of this coordination under chronic stress remain poorly understood. Here, we show that 5 y of chronic soil moisture limitation fundamentally constrains the capacity of leaves to maintain adequate thermoregulation. Focusing on two temperate tree species with contrasting water-use strategies, European beech ( Fagus sylvatica ) and downy oak ( Quercus pubescens ), which were subjected to a 5-y manipulation of soil moisture and air temperature, we tested how acclimation influences leaf thermoregulation, hydraulic safety margins (HSMs), thermal safety margins (TSMs), and leaf scorching. Under sustained heating with ample soil water availability, both species acclimated to maintain stable leaf temperature and positive TSMs despite warmer conditions, demonstrating that thermal acclimation is possible without hydraulic stress. By contrast, chronic soil drought narrowed HSMs and weakened evaporative cooling, reducing leaf thermoregulation capacity. When drought and heat co-occurred, stomatal closure triggered a runaway feedback loop: Impaired water transport led to loss of cooling, causing breaching of critical thermal thresholds. These events coincided with failures of photosystem II and scorching in drought-vulnerable beech, linking drought-induced stomatal limitation directly to thermal injury. Our results reveal that oak and beech can acclimate to warming alone, but not to simultaneous heat and drought, which together drive a hydraulic–thermal cascade exceeding both safety margins. This interaction sets fundamental limits on the resilience of temperate forests to future hot droughts.